A comparison of fabric structures for carbon fiber reinforced composite: Laminated and orthogonal woven structures. Issue 10 (17th July 2021) - Yang, Tao; Hu, Lizhu; Xiong, Xiaoman; Wang, Yuanfeng; Wang, Xiaomeng; Petrů, Michal; Zhang, Shangyong; Mishra, Rajesh; Militký, Jiří
Abstract: In this research, orthogonal structure carbon fiber reinforced composite was developed and its properties were compared with those of laminated structure composite. To solve the problem of yarn damage caused by friction during the weaving process, a custom‐built weaving device was build up. Compression and vacuum‐assisted resin infusion molding (VARIM) techniques were selected and compared. It was found that fiber geometries could be well retained using the later one. The orthogonal and laminated composites prepared by the VARIM technique with the fiber volume fraction were 32.76% and 38.64%, respectively. Flexure and impact tests were performed to evaluate the properties of laminated and orthogonal composites. The results show that orthogonal composite exhibits superior properties in the warp and weft directions. In addition, due to its straight yarn path and insertion of carbon fiber in the through‐thickness direction, orthogonal fabric reinforced composite exhibits an improved bending strength over composites reinforced by laminated plain woven fabric, although the fiber volume fraction of orthogonal composite is much lower than that of laminated composite. The findings indicate that orthogonal structure composite provides profound guiding significance for product development and application of carbon fiber composite. Abstract :